Mixotrophic Plankton in the Polar Seas: A Pan-Arctic Review - Stoecker, Diane K.; Lavrentyev, Peter J. (Frontiers in Marine Science, 2018)
Polar marine ecosystems are characterized by low water temperatures, sea ice cover, and extreme annual variation in solar irradiance and primary productivity. A review of the available information from the Arctic suggests that mixotrophy (i.e. the combination of photosynthetic and phagotrophic modes of nutrition in one cell) is wide spread among plankton. In the central Arctic Ocean (AO) in summer, mixotrophic flagellates such as Micromonas and Dinobryon can account for most of bacterivory. Planktonic ciliates with acquired phototrophy form the bulk of microzooplankton biomass in both the ultra-oligotrophic deep basins of AO and its productive shelf seas. With the exception of the diatom bloom in the marginal ice zone, mixotrophic ciliates often dominate total chlorophyll in the mixed layer in summer taking advantage of the 24-h insolation. Their relatively high growth rates at low temperatures indicate that they are important component of primary and secondary production. The key Arctic copepod species preferentially feed on chloroplast-bearing ciliates, which form an important link in the planktonic food web. The limited year round data indicate that are available show that mixotrophic plankton persist in the water column during the long polar winter when irradiance is low or absent and ice cover reduces further light penetration. These observations suggest that at high latitudes an alternative food web based on mixotrophy may dominate the pelagic lower food web during much of the year.